Analysis of Wigner energy release process in graphite stack of shut-down uranium-graphite reactor; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Bespala E. V. Evgeniy (Evgeny) Vladimirovich (Physical methods in science and engineering, 2015)
Title screen